Cross-Feeding of Lactate Between Streptococcus lactis and Bacteroides sp. Isolated from Termite Hindguts - Schultz, J. E. (1979)
Streptococcus lactis and Bacteroides sp., isolated from hindguts of Reticulitermes flavipes termites, were grown anaerobically in monoculture and coculture. When grown in a glucose medium, S. lactis monoculture produced lactate as the major fermentation product, with small amounts of formate, acetate, ethanol, and CO(2). In coculture, glucose was completely consumed during growth of S. lactis. Lactate, produced by S. lactis, then supported much of the growth of Bacteroides and was fermented to propionate, acetate, and CO(2). Small amounts of succinate were formed during growth of Bacteroides in the coculture, but little change in the formate or ethanol concentration was observed. Monoculture growth of Bacteroides in a tryptone-yeast extract medium revealed that incorporation of 20 to 40 mM lactate increased cell yields and production of organic acids. However, initial lactate concentrations greater than 40 mM suppressed not only growth of Bacteroides but also acidic product formation. Results suggest that cross-feeding of lactate between streptococci and bacteroides constitutes one aspect of the overall hindgut fermentation in termites.